Pengendalian Kualitas Produk Kompon E-1440 Part Number 7105 - 4764 Menggunakan Metode Seven Tools - Ambarwati, Sukma; Diem, Daisy Ade Riany; Setiadewi, Elly (Universitas Muhammadiyah Sorong, 2025)
The effectiveness of the production process and product quality are crucial in determining how well a company competes. Product quality is one of the main factors in determining the success of a company. PT. XYZ is a manufacturing company engaged in the automotive rubber spare parts industry. One of the products produced is the EPDM-1440 rubber compound or can also be called the E-1440 compound. The E-1140 compound that has been turned into a rubber product has a part number. This study aims to identify the most dominant type of defect or so-called NG (Not Good) and analyze the causes of defects in the E-1440 compound product Part Number 7015-4764 at PT. XYZ. The research method used is the Seven Tools, which includes histograms, Pareto diagrams, fishbone diagrams, U-control charts, and Why-Why Analysis. Based on data for six months September 2024 - February 2025, it was found that the NG type of slit tear was the most dominant with a total of 375 units (37.24%). The U control chart shows that there are data points that are outside the control limits, therefore a revision is made to the data that is outside the control limits and the average product damage (CL) is 0.007, the upper control limit (UCL) is 0.020 and the lower control limit (LCL) is -0.005. The main cause of the emergence of NG torn slits is due to humans, then improvements are proposed by focusing on improving operator training..